A Research Model to Determine the Applicability of American Management Know-How in Differing Cultures and/or Environments - Negandhi, Anant R.; Estafen, Bernard D. (Academy of Management Journal, 1965)
Addressing the concern of many that management is culture-bound and others who believe that management is governed by universal principles, the article discusses cross-cultural research in the area of management science. In an effort to identify those American management practices that are transferable, and those that are not, the article seeks to identify those external environmental factors which would have an impact on management. The article focuses on management philosophy, process, and effectiveness and proposes a method of study and a model of the authors' ideas.